Foreign exchange : counterculture behind the walls of St. Hilda's School for Girls, 1929-1937 - Liu, Judith, 1950- (Studies in missionaries and Christianity in China., 2011)
Foreign Exchange is the story of two women and their experiences at an American Episcopalian missionary school in Wuhan St. Hilda's School for Girls from 1929-1937. Yeh Yuanshuang was a student from a privileged Chinese family; Dorothea Kingsley Wakeman was a short-term teacher from a privileged American family. Both would be transformed by their experiences at St. Hilda's whose walls served to protect the school from outside danger as well as to help create a space where new gender expectations could be nurtured, hidden away from the gaze of prying eyes.